1995
DOI: 10.1063/1.114688
|View full text |Cite
|
Sign up to set email alerts
|

New synthesis method of fullerenes using microwave-induced naphthalene-nitrogen plasma at atmospheric pressure

Abstract: A new synthesis method of fullerenes has been investigated for microwave induced naphthalene-nitrogen plasma at atmospheric pressure using a cylindrical coaxial cavity. The toluene extract solution of soot obtained after discharges showed HPLC peaks with retention times corresponding well to those of C60 and C70. The production of fullerenes was also confirmed by mass-spectrometric analysis. Gas temperature of nitrogen plasma determined from radiative transitions of N2+ was 3800–5700 K. From a comparison of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…The research on the development of fullerenes was written by T. I. Ikeda et al (1995). They investigated the microwave-induced naphthalene-nitrogen plasma at atmospheric pressure via a cylindrical coaxial cavity [211].…”
Section: Microwavementioning
confidence: 99%
“…The research on the development of fullerenes was written by T. I. Ikeda et al (1995). They investigated the microwave-induced naphthalene-nitrogen plasma at atmospheric pressure via a cylindrical coaxial cavity [211].…”
Section: Microwavementioning
confidence: 99%
“…10 In recent years, several synthetic routes were reported to produce doped fullerenes and nanotubes. 11,12 In the pioneering works of Pradeep et al 13 and Guo et al 14 respectively, nitrogen and boron substitution of fullerenes were reported. The possibility of having a new family of closed molecular shapes containing atoms other than carbon encouraged researchers into looking for ''heterofullerenes.''…”
Section: Introductionmentioning
confidence: 99%
“…Their relatively high superconductivity (1)(2)(3)(4), together with the large family of new compounds that can be prepared from fullerenes (5), make them an interesting research area for today's investigators. Scientists have been engaged to find new production methods for fullerenes other than arc vaporization of graphite electrodes, including high temperature pyrolysis or combustion of aromatic molecules (8)(9)(10)(11) and plasma dissociation (12)(13)(14)(15), to obtain larger quantities of these fantastic molecules. Scientists have been engaged to find new production methods for fullerenes other than arc vaporization of graphite electrodes, including high temperature pyrolysis or combustion of aromatic molecules (8)(9)(10)(11) and plasma dissociation (12)(13)(14)(15), to obtain larger quantities of these fantastic molecules.…”
Section: Introductionmentioning
confidence: 99%